(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article provides a lexical and semantic analysis of the development of euphemistic, gender-polite vocabulary in the Russian and Uzbek languages. It examines the functions of euphemization , its national and cultural characteristics, and the mechanisms of its formation, including metaphorization, paraphrasing, borrowings, and morphological and syntactic mitigation strategies. Particular attention is paid to specific thematic groups of euphemisms: those related to the intimate and bodily sphere, age characteristics, appearance, and family and professional roles. A comparative analysis is conducted, revealing common trends and differences in approaches to gender-polite communication, conditioned by cultural, religious, and social factors. The article demonstrates the dynamic development of euphemistic vocabulary in both languages and its significance for understanding modern speech etiquette and gender communication.